Evidence to Support Universal Blood Pressure Screening in School‐Based Clinical Settings. (31st March 2020) - Silberstein, Juliet; Gwynn, Lisa; Mathew, M. Sunil; Arheart, Kristopher L.; Messiah, Sarah E.
ABSTRACT: BACKGROUND: Most pediatric elevated blood pressure (BP) remains undiagnosed. The American Academy of Pediatrics states "there is limited evidence to support school‐based measurement of children's BP." We explored the utility school‐based BP screening. METHODS: A cross‐sectional sample of 4096 students ages 6 to 17 from Title 1 Miami‐Dade Public Schools (50% female, 71% non‐Hispanic black, 26% Hispanic) had their systolic/diastolic BP (SBP/DBP) and body mass index (BMI) collected over the 2016 to 2017 or 2017 to 2018 school years. Relative risks (RRs) ratios were calculated to estimate normal/elevated SBP/DBP by BMI percentile, ethnicity, and sex. RESULTS: Overall, 26.4% had at least one elevated BP measurement, of which 59% were not obese. RR for obese status was significant for all categories of elevated BP (RRs > 1.88, p < .0001). Being either female (RR = 1.34, p = .009) or Hispanic (RR = 1.31, p = .014) was significantly associated with elevated DBP. BMI accounted for <10% of the variation in BP (SBP: F(1, 4095) = 367.6, adjusted R 2 = .08, p < .0001; DBP: F(1, 4095) = 93.3, adjusted R 2 = .02, p < .0001). CONCLUSION: These findings support providing BP screenings in school settings. Low‐income and minority students often have limited access to health care, higher obesity rates, and unhealthy behaviors. Our findings support universal school‐based BP screening regardless of weight status, particularly among ethnically diverse populations.